Study on the Utilization of Banana Stem and Rice Bran Waste as a Biogas Source for Electric Power Generation - Gusti Komang Apriadi, I; Ilham, Jumiati; Irawaty Tolago, Ade; Ismail Yusuf, Taufiq (Emitor: Jurnal Teknik Elektro, 2026)
The increasing volume of agricultural waste, particularly banana stems and rice bran, presents an environmental challenge due to improper disposal and underutilization. This study aims to address this issue by using these wastes as alternative raw materials for biogas production through a 25-day anaerobic fermentation process. Three substrate variations were tested: 100% banana stem, 100% rice bran, and a 50:50 mixture of both. The observed parameters included methane gas concentration (CH₄), pH, temperature, biogas pressure, flame quality, and electrical energy conversion. Results indicated that the mixed substrate produced the highest methane concentration of 101.07 ppm, pressure of 104,266.99 Pa, and a stable blue flame lasting 16 minutes 25 seconds. The pH values range between 6.5–7.1 under mesophilic temperatures (30–36.5°C). The highest electrical energy output was 0.321391 kWh from the mixed substrate. These findings demonstrate that combining banana stem and rice bran substrates is more efficient for biogas generation and has strong potential as a renewable energy source for sustainable applications.